Response of dry season sorghum to supplemental irrigation and fertilizer N and P on Vertisols in northern Cameroon - Carsky, R.J.; Ndikawa, R.; Singh, L.; Rao, M.R. (Elsevier, 1995)
A series of trials was conducted to quantify response of dry season transplanted sorghum to water and fertilizer application in order to test the hypothesis that soil moisture limits production more than nutrient supply. The trials were conducted at two field sites representative of a large land area in the Lake Chad Basin of Africa. Water was clearly the limiting factor as grain yield response to two irrigations (10 cm total) was a statistically significant 58% over 3 years. One irrigation during vegetative growth resulted in sorghum grain yield increases of 24–29%. Response to P fertilizer was negligible. Response to N fertilizer was 32% over three environments but was not statistically significant at P < 0.05. Future research should focus on improvements in soil moisture availability, either through increased soil moisture storage or through reduced evaporative losses.